Analytical Solution of Diffraction by a Composite Cylinders Above a Special Bottom Undulation in Uniform Water - Hassan, M.; Tashi, L. (Communications in Mathematics and Applications, 2022)
We consider the co-axial cylindrical structure as a composite submerged solid cylinder above a special bottom undulation, i.e., a circular plate at the impermeable horizontal bottom. We consider the diffraction problem of the proposed structure in water of finite depth. This diffraction problem can be expressed as a wave energy converter. The variables of separation and eigenfunction expansion methods are utilized to determine the analytical solutions for the diffraction problem in their identified sub-domains. By using the methods of expansion of eigenfunction and the orthogonality of Bessel functions to the expression of the diffracted velocity potentials. We achieve a system of linear equations after suitably truncated to the obtain infinite series. This work may be helpful to the wave designer to design appropriate device so that one can extract maximum wave energy. The created wave energy may be used in many applications of conventional energy.
Keywords: Diffraction; Uniform depth; Virtual boundary; Exciting forces; Analytical solution